Upgrading Manual Turning Machine Towards IoT-Based Manufacturing - Sutopo, Sutopo; Setiadi, Bayu Rahmat; Hanzla, Muhammad (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
Technological independence is one aspect of the challenges of the industrial revolution era 4.0. Digitalization, robotization, big data, internet of things (IoT), and efficiency of work processes require an update in technology. If everything is held in the fulfillment of practicum facilities, it will undoubtedly cost a prohibitive fee. Many of the tools and machines found in learning machining practices in Vocational High Schools (VHS) in Indonesia are still a conventional machine. This study provides a breakthrough solution in the effectiveness and efficiency of traditional machining of the lathe that starts with a preliminary identification of literature, selection according to inclusion and exclusion criteria, coding, themes classifications, and supplementary areas. Through the literature review methodology, this article has the main objective of identifying the needs in architecture and the need for supporting devices on conventional lathes based on the IoT as well as safe, comfortable, and modern work areas in lathe machining practices.